A novel coculture model of HUVECs and HUASMCs by hyaluronic acid micropattern on titanium surface. Issue 6 (30th July 2013) - Li, Jingan; Zhang, Kun; Xu, Ying; Chen, Jiang; Yang, Ping; Zhao, Yuancong; Zhao, Ansha; Huang, Nan
Abstract Orientation smooth muscle cell environment plays a positive role in the development of a functional, adherent endothelium. Therefore, building an orientation coculture model of endothelial cells (ECs) and smooth muscle cells (SMCs) on biomaterials surface may provide more help for understanding the interaction between the two cells in vitro. In the present study, a "SMCs‐ColIV‐ECs" coculture model was built on the hyaluronic acid (HA) patterned titanium (Ti) surface, and compared with the previous "SMCs‐HAa‐ECs" model on endothelial cell number, morphology index, nitric oxide (NO), and prostacyclin2 (PGI2) release, anticoagulation property, human umbilical artery smooth muscle cells (HUASMCs) inhibition property and retention under fluid flow shear stress. The result indicated that "SMCs‐ColIV‐ECs" model could enhance the number, spreading area, and major/minor index of human umbilical vein endothelial cells (HUVECs), which contributed to the retention of HUVECs on the surface. Greater major/minor index may produce more NO and PGI2 release, contributing to the anticoagulation property and HUASMCs inhibition property. In summary, this novel "SMCs‐ColIV‐ECs" coculture model improved the previous "SMCs‐HAa‐ECs" model, and may provide more inspiration for the human vascular intima building on the biomaterials in vitro. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1950–1960, 2014.